2017
DOI: 10.1001/jamaoncol.2016.5630
|View full text |Cite|
|
Sign up to set email alerts
|

Intrinsic Subtype Switching and Acquired ERBB2/HER2 Amplifications and Mutations in Breast Cancer Brain Metastases

Abstract: IMPORTANCE Patients with breast cancer (BrCa) brain metastases (BrM) have limited therapeutic options. A better understanding of molecular alterations acquired in BrM could identify clinically actionable metastatic dependencies. OBJECTIVE To determine whether there are intrinsic subtype differences between primary tumors and matched BrM and to uncover BrM-acquired alterations that are clinically actionable. DESIGN, SETTING AND PARTICPANTS In total, 20 cases of primary breast cancer tissue and resected BrM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 16 publications
10
117
0
1
Order By: Relevance
“…Finally, considering that we have previously shown that brain metastases acquire highly recurrent gains in clinically actionable genes following colonization (13), particularly in HER2, we analyzed an expanded set of these genes in BoMs. All tumors harbored significant gains and losses, some of which were highly recurrent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, considering that we have previously shown that brain metastases acquire highly recurrent gains in clinically actionable genes following colonization (13), particularly in HER2, we analyzed an expanded set of these genes in BoMs. All tumors harbored significant gains and losses, some of which were highly recurrent.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these observations provide further evidence of acquired transcriptional remodeling in metastatic lesions and suggest that precision care in advanced cancers may benefit from defining longitudinal changes in tumor transcriptomes. Further research into these longitudinal transcriptional remodeling events is demanded -especially given their high recurrence rates -including identifying events that may be specific or more likely to occur in metastases from certain anatomic sites, such as HER2 gains in brain metastases (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal studies that involve serial assessment of multiple tissue and liquid biopsies also reflect changes in sub-clonal populations that correspond to disease progression and differential responses to therapy [38]. Importantly, there is evidence that demonstrates intrinsic subtype switching in breast cancer brain metastases relative to primary tumors [39]. In this particular study, molecular changes in Her2 and intrinsic subtype switching to Her2-enriched subtypes can be associated with brain metastasis, indicating that the brain micro-environment may favor the progression of Her2 driven malignancies.…”
Section: Plasticity Of Breast Cancer Subtypesmentioning
confidence: 99%